2012
DOI: 10.2332/allergolint.11-oa-0307
|View full text |Cite
|
Sign up to set email alerts
|

Niflumic Acid Inhibits Goblet Cell Degranulation in a Guinea Pig Asthma Model

Abstract: NFA inhibited the secretory response of mucus granules in an asthma model, suggesting that CLCA may be associated with goblet cell degranulation and that CLCA inhibitors may be useful for the treatment of hypersecretion in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…Consistent with a previous report (6), we did not detect TMEM16A in association with mucins in secretory vesicles. A recent study showed that the nonspecific chloride channel blocker NFA inhibits the secretion of mucus granules in guinea pig asthma models, further supporting our hypothesis that CaCC may be associated with goblet cell degranulation, and CaCC inhibitors may be useful for the treatment of hypersecretion in asthma (55). In addition to the respiratory epithelium, we detected TMEM16A expression in ASM.…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with a previous report (6), we did not detect TMEM16A in association with mucins in secretory vesicles. A recent study showed that the nonspecific chloride channel blocker NFA inhibits the secretion of mucus granules in guinea pig asthma models, further supporting our hypothesis that CaCC may be associated with goblet cell degranulation, and CaCC inhibitors may be useful for the treatment of hypersecretion in asthma (55). In addition to the respiratory epithelium, we detected TMEM16A expression in ASM.…”
Section: Discussionsupporting
confidence: 68%
“…Those genes (particularly Ear11 and Clca3) that were regulated by both MWCNT and αST2-blocking Ab experimental conditions were considered of particular interest. Indeed, although the exact mechanisms remain unknown, Ear11 and Clca3 have previously been implicated in asthma pathology (Di Valentin et al 2009; Zhou et al 2001; Kondo et al 2012) and may represent suitable therapeutic targets to mediate Th2-associated inflammation. Experiments are currently underway in our laboratories to better understand the contributions of Ear11 and Clca3 expression to the IL-33/ST2 signaling axis and their importance to the establishment of Th2-associated inflammation following MWCNT exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, niflumic acid (0.64 mg/kg) significantly inhibited the Mch-induced decrease in C dyn (P , 0.0005, OVA-sensitized mice with and without niflumic acid). Because niflumic acid was administered 5 minutes before Mch application, it is unlikely that the effect of niflumic acid on lung function resulted from its influence on cytokine production, mucin synthesis, or goblet cell degranulation (9)(10)(11). To validate this, we examined the effect of niflumic acid on IL-17, a cytokine critical to the pathogenesis of asthma in this mouse model (30).…”
Section: Resultsmentioning
confidence: 99%